Answer:
D. ![\sqrt{65}](https://tex.z-dn.net/?f=%5Csqrt%7B65%7D)
Step-by-step explanation:
The computation of the length of a diagonal (AC or BD) of the rectangle is shown below:
As we know that
The Diagonal length of AC is
![= (x_2 - x_1)^2 + (y_2 - y_1)^2\\\\= (9 -2)^2 + (8 - 4)^2\\\\= (7)^2 + (4)^2](https://tex.z-dn.net/?f=%3D%20%28x_2%20-%20x_1%29%5E2%20%2B%20%28y_2%20-%20y_1%29%5E2%5C%5C%5C%5C%3D%20%289%20-2%29%5E2%20%2B%20%288%20-%204%29%5E2%5C%5C%5C%5C%3D%20%287%29%5E2%20%2B%20%284%29%5E2)
![= \sqrt{49 + 16}\\\\= \sqrt{65}](https://tex.z-dn.net/?f=%3D%20%5Csqrt%7B49%20%2B%2016%7D%5C%5C%5C%5C%3D%20%5Csqrt%7B65%7D)
Therefore correct option is D.
Answer:
Table B
Step-by-step explanation:
Table A Input Output
5 3
5 2
4 1
Has an input that goes to 2 different outputs, not a function
Table B Input Output
1 2
3 2
5 3
one to one relation which is a function
Table C Input Output
0 0
1 2
1 3
Has an input that goes to 2 different outputs, not a function
Table D Input Output
4 2
4 3
4 4
Has an input that goes to 2 different outputs, not a function
A prime number can only be divided by one oritslef and a composite number can bedivided by other njmbers.
Answer:
x = -14
Step-by-step explanation:
Simplifying
7x + 156 = 9x + 184
Reorder the terms:
156 + 7x = 9x + 184
Reorder the terms:
156 + 7x = 184 + 9x
Solving
156 + 7x = 184 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
156 + 7x + -9x = 184 + 9x + -9x
Combine like terms: 7x + -9x = -2x
156 + -2x = 184 + 9x + -9x
Combine like terms: 9x + -9x = 0
156 + -2x = 184 + 0
156 + -2x = 184
Add '-156' to each side of the equation.
156 + -156 + -2x = 184 + -156
Combine like terms: 156 + -156 = 0
0 + -2x = 184 + -156
-2x = 184 + -156
Combine like terms: 184 + -156 = 28
-2x = 28
Divide each side by '-2'.
x = -14
Simplifying
x = -14
Since both are equivalent to y, the equations must be equivalent.
x^2-x-3= -3x+5
x^2+2x-8=0
(x+4)(x-2)=0
x=-4, x=2
Plug the values of x in to either equation
y=-3(-4)+5
y= 12+5
y=17
y= -3(2)+5
y=-6+5
y=-1
Final answer: (-4,17) and (2,-1)